PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, LEVERAGE, DAN STRUKTUR KEPEMILIKAN INSTITUSIONAL TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL MODERASI - Fadhilah, Rifky; Idawati, W; Praptiningsih, Praptiningsih (Jurnal Akunida, 2021)
The study is aimed at assessments of corporate performance, Leverage, and institutional ownership of corporate social holdings as moderate variables of the company's corporate holdings listed at the Indonesian stock exchange. The study is a quantitative used a secondary file of annual company reports. This study sample is 307 manufacturing companies. The data analysis with classic assumptions test, regression analysis tests, and hypothetical tests. Data analysis suggests that (1) firm size has a negative signifanct impact on firm value, (2) profitability has a positive significant impact on firm value, (3) Leverage has a positive significant impact on firm value, (4) institutional ownership does not significantly affect on firm value, (5) Corporate Social Responsibility has a role in modernizing firm size relationships with firm value, (6) Corporate Social Responsibility has no role in moderating profitability relationships with firm value, (7) Corporate Social Responsibility has no role in moderating Leverage relationships with firm value, and (8) Corporate Social Responsibility has no role in moderating institutional ownership relationships with firm value.